Synthesis of ultra-high molecular weight homo- and copolymers via an ultrasonic emulsion process with a fast rate - Uddhab Kalita; Vianna F. Jafari; Muthupandian Ashokkumar; Nikhil K. Singha; Greg G. Qiao (Communications Chemistry, 2024)
Abstract In the forefront of advanced materials, ultra-high molecular weight (UHMW) polymers, renowned for their outstanding mechanical properties, have found extensive applications across various domains. However, their production has encountered a significant challenge: the attainment of UHMW polymers with a low dispersity (Ɖ). Herein, we introduce the pioneering technique of ultrasound (US) initiated polymerization, which has garnered attention for its capability to successfully polymerize a multitude of monomers. This study showcases the synthesis of UHMW polymers with a comparatively low Ɖ ( ≤ 1.1) within a remarkably short duration ( ~ 15 min) through the amalgamation of emulsion polymerization and high-frequency ultrasound-initiated polymerization. Particularly noteworthy is the successful copolymerization of diverse monomers, surpassing the molecular weight and further narrowing the Ɖ compared to their respective homopolymers. Notably, this includes monomers like vinyl acetate, traditionally deemed unsuitable for controlled polymerization. The consistent production and uniform dispersion of radicals during ultrasonication have been identified as key factors facilitating the swift fabrication of UHMW polymers with exceptionally low Ɖ.